Sustainable Food Sovereignty, a Biocultural Approach to Feeding - Julie Cecilia Hernández Medina; Eduardo Andrés Sandoval Forero; Javier Jesús Ramírez Hernández; Fredyd Torres Oregón (International Journal of Agricultural Sciences, 2021)
There are different relationships between people and nature. One of them is about the satisfaction of a basic need for survival: feeding, which in addition to being a human right, is also one of the most important concerns in the world since there are high levels of malnutrition, obesity, insufficiency, and food insecurity. One of the proposals to understand the link between people and nature related to feeding is food sovereignty, which was conceived by civil society to re-signify the role of peasants and their autonomy. This paper is a result of a theoretical reflection to propose a different vision of food sovereignty based on sustainability. Sustainable food sovereignty could promote the visibility and improvement of the different relationships between people and nature throw sustainable agriculture, self-consumption and sustainable consumption, and fair distribution and trade